2017
DOI: 10.18088/ejbmr.1.1.2015.pp22-27
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid inhibits the amyloid fibrils formation of β-lactoglobulin

Abstract: Abstract:It is well known that amyloid fibrils are associated with a lot of neurodegenerative diseases. Thus, inhibition of protein aggregation and disruption of the formed amyloid fibrils have been attractive therapeutic strategies for amyloid-associated diseases. Here, we take the widely studied protein, β-lactoglobulin (β-LG), as a model protein to study the inhibition of amyloid fibrils. Using multiple biophysical and biochemical approaches, we successfully identify that folic acid can strongly inhibit amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The insulin sensitizing effects of CLA were relative to activation of PPAR γ at least in part. It was predicted that the antidiabetes mechanism of CLA is similar to thiazolidinedione, an antidiabetic medicine (37)(38)(39)(40).…”
Section: Unsaturated Fatty Acidmentioning
confidence: 99%
“…The insulin sensitizing effects of CLA were relative to activation of PPAR γ at least in part. It was predicted that the antidiabetes mechanism of CLA is similar to thiazolidinedione, an antidiabetic medicine (37)(38)(39)(40).…”
Section: Unsaturated Fatty Acidmentioning
confidence: 99%
“…Moreno et al indicated that the grape seed extract with rich bioactive phytochemicals, showed strong inhibitory activity against the fat-metabolizing enzymes pancreatic lipase and lipoprotein lipase. Besides, the observed reduction in intracellular lipolytic activity of cultured 3T3-L1 adipocytes may reduce the levels of circulating free fatty acids that have been linked to insulin resistance in obese patients (13,14). In addition, it has been suggested that twelve flavonoids isolated from Glycyrrhiza glabra roots inhibited pancreatic lipase activity in a dose-dependent manner, which therefore reduced the intestinal absorption of dietary fats and regulated lipid metabolism (15).…”
Section: Introductionmentioning
confidence: 99%